2018
DOI: 10.1080/14767058.2018.1475643
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between presepsin and procalcitonin in early diagnosis of neonatal sepsis

Abstract: In early diagnosis of neonatal sepsis, compared with procalcitonin, presepsin seems to provide better early diagnostic value with consequent possible faster therapeutical decision making and possible positive impact on outcome of neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
1
22
0
2
Order By: Relevance
“…No better than PCT regardless of the presence or not of AKI [17] Neonates with SIRS and positive blood cultures Neonates with SIRS with negative blood cultures Better than PCT [81] Better performance when combined with PCT and/or CRP…”
Section: Patients With Proven Viral Lower Respiratory Infectionmentioning
confidence: 99%
“…No better than PCT regardless of the presence or not of AKI [17] Neonates with SIRS and positive blood cultures Neonates with SIRS with negative blood cultures Better than PCT [81] Better performance when combined with PCT and/or CRP…”
Section: Patients With Proven Viral Lower Respiratory Infectionmentioning
confidence: 99%
“…It should again be recognised that the patient cohorts in these studies were fairly small (fewer than 50 in most) which must be considered as a limiting factor. A similarly sized study reported a lower AUC of 0.758 for presepsin, while also reporting an AUC of 0.599 for PCT [55]. The value for PCT was also lower than has generally been reported in other studies considered previously.…”
Section: Neonatesmentioning
confidence: 48%
“…In the neonatal group, they suggested that PCT has moderate diagnostic accuracy, but further studies are required. A more recent study that investigated the use of presepin and PCT for the diagnosis of early neonatal sepsis also suggested that PCT performed relatively poorly, calculating the area under the curve (AUC) for PCT as 0.599 [55]. This study did have some limitations in that the study group was fairly small (51 neonates) and there was no defined control group.…”
Section: Neonatesmentioning
confidence: 96%
“…In the last few years, PCT has been investigated as a promising early biomarker in the diagnosis of neonatal infections and different results have been published [17], [27] . In these studies, PCT values ranged from 0.5 to 25 ng/mL [23] , the reported PCT sensitivity for the diagnosis of early onset sepsis was found to be 30-100% while the specificity was 51-100% [17] .…”
Section: Resultsmentioning
confidence: 99%